LipidomeDB data calculation environment: Online processing of direct-infusion mass spectral data for lipid profiles - Zhou, Zhenguo; Marepally, Shantan Reddy; Nune, Daya Sagar; Pallakollu, Prashanth; Ragan, Gail; Roth, Mary R.; Wang, Liangjiang; Lushington, Gerald H.; Visvanathan, Mahesh; Welti, Ruth (My University, 2011)
LipidomeDB Data Calculation Environment (DCE) is a web application to quantify complex lipids by processing data acquired after direct infusion of a lipid-containing biological extract, to which a cocktail of internal standards has been added, into an electrospray source of a triple quadrupole mass spectrometer. LipidomeDB DCE is located on the public Internet at http://lipidome.bcf.ku.edu:9000/Lipidomics. LipidomeDB DCE supports targeted analyses; analyte information can be entered, or pre-formulated lists of typical plant or animal polar lipid analytes can be selected. LipidomeDB DCE performs isotopic deconvolution and quantification in comparison to internal standard spectral peaks. Multiple precursor or neutral loss spectra from up to 35 samples may be processed simultaneously with data input as Excel files and output as tables viewable on the web and exportable in Excel. The pre-formulated compound lists and web access, used with direct-infusion mass spectrometry, provide a simple approach to lipidomic analysis, particularly for new users.
Keywords: Triple quadrupole mass spectrometry; Precursor scan; Neutral loss scan; Direct infusion; Lipid quantification; Lipidomics